Порівняння класифікації зображень хромаграм і спектрограм для розпізнавання акордів - Пономаренко, А. О. (ХНУРЕ, 2023)
This work is devoted to a comparison of a usage of a chroma and a spectrogram for a chord recognition. Image classification is one of fields of neural networks usage. After a model is learned by annotated images it can be used to recognize a class of another one. This approach is appliable also for sounds. And the problem is how to represent a sound as an image. There are different ways. The choice depends on the domain. In the chord recognition a tone frequency is the most important part. There are two representation of the sound tones – spectrogram and chroma. The spectrogram shows the dependence of the signal power spectral density on time. A chromogram is a spectrogram, but the signal is divided into 12 logarithmically distributed parts that corresponds to 12 notes